2012
DOI: 10.3109/17482968.2012.678366
|View full text |Cite
|
Sign up to set email alerts
|

Reduction rate of body mass index predicts prognosis for survival in amyotrophic lateral sclerosis: A multicenter study in Japan

Abstract: Malnutrition in the early stage has been reported as an independent predictor of survival in amyotrophic lateral sclerosis (ALS). We analyzed retrospectively the effect of variation of body mass index (BMI) on survival in ALS patients. In total, 77 consecutive ALS patients were enrolled from nine hospitals in Japan. Reduction rate of BMI was calculated from BMI before the disease onset and at the time of the first visit to each hospital. We analyzed the correlation between BMI reduction rate and total disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 13 publications
2
73
1
Order By: Relevance
“…Another reason could be the inclusion of patients in the early stages of the disease where the respiratory functions were not affected; a fact that would help the preservation of body fat reserves. The importance of multidisciplinary assessment in the literature is well described, including early nutritional counseling as a positive factor for maintaining the nutritional status with a preventive approach in the treatment of ALS 14,15,16,19 . Although there was a variation in BMI, it was not enough to change the classification of nutritional status, stressing that as an isolated measure, the BMI is not sensitive enough to detect body alteration in the course of the disease 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another reason could be the inclusion of patients in the early stages of the disease where the respiratory functions were not affected; a fact that would help the preservation of body fat reserves. The importance of multidisciplinary assessment in the literature is well described, including early nutritional counseling as a positive factor for maintaining the nutritional status with a preventive approach in the treatment of ALS 14,15,16,19 . Although there was a variation in BMI, it was not enough to change the classification of nutritional status, stressing that as an isolated measure, the BMI is not sensitive enough to detect body alteration in the course of the disease 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of multidisciplinary assessment in the literature is well described, including early nutritional counseling as a positive factor for maintaining the nutritional status with a preventive approach in the treatment of ALS 14,15,16,19 . Although there was a variation in BMI, it was not enough to change the classification of nutritional status, stressing that as an isolated measure, the BMI is not sensitive enough to detect body alteration in the course of the disease 16 . Muscle atrophy is itself the triggering factor of changes, justifying the periodic anthropometric evaluation, with a recommendation for the anthropometry of the arm 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this finding is malnutrition [12,23], and as shown in this study, the BMI was significantly lower in bulbar onset patients (Table 1). Additionally, it has been observed that these patients have an increased risk of aspiration and earlier respiratory distress [21].…”
Section: Discussionmentioning
confidence: 61%